Butterfly Pea (Clitoria Ternatea L.) Extract as Indicator of Acid-Base Titration - Bayu Wiyantoko; Astuti astuti (Universitas Islam Indonesia, 2020)
An anthocyanin color pigment result from butterfly pea flower maceration has been done. This study aims to determine the effect of time variation in the maceration of anthocyanin butterfly pea flower extract and the stability of butterfly pea flower extract as an indicator of acid-base titration. Color pigment levels were determined quantitatively with a UV-Visible spectrophotometer. The anthocyanin levels obtained during the duration of maceration 5 days in a row resulted from 4.3915%, 5.9869%, 7.3970%, 8.8995%, and 10.2864%. While the anthocyanin levels using a differential pH method were 14.2775 mg/L and 14.9455 mg/L with % RPD value was 4.57%. The results of the study stated that the indicators of the butterfly pea flower crown extract can be a substitute for the synthetic phenolphthalein indicator that has been used.